Chapter L'immagine di Firenze e Bologna in Obrazy Italii di Pavel Muratov: riflessioni sulla traduzione del lessico artistico - Perotto, Monica (Lessico multilingue dei Beni Culturali, 2023)
This chapter focuses on Obrazy Italii, the best known work by Pavel Muratov, a Russian writer, journalist, critic and art historian. This work is a diary recounting the journey to Italy of the author at the beginning of the twentieth century; nowadays it is considered a classic text that provides a testimony on the way Italian art was perceived in Russia. Though it is well-known in Russia, this work has only recently received some attention in Italy following its recent translation. This chapter contains detailed and original analyses that compare Muratov's translations with those found in Russian dictionaries written in the same period. These concern a selection of lemmas in art and architecture and the names of artists. This chapter shows that the language employed in this work cannot be defined as either specialised or standard, but as a mixture between the two.